Periconceptional surveillance for prevention of anaemia and birth defects in Southern India: protocol for a biomarker survey in women of reproductive age. Issue 10 (29th October 2020) - Finkelstein, Julia L; Fothergill, Amy; Johnson, Christina B; Guetterman, Heather M; Bose, Beena; Jabbar, Shameem; Zhang, Mindy; Pfeiffer, Christine M; Qi, Yan Ping; Rose, Charles E; Krisher, Jesse T; Ruth, Caleb J; et al.
Abstract : Introduction: Women of reproductive age (WRA) are a high-risk population for anaemia and micronutrient deficiencies. Evidence supports the role of periconceptional nutrition in the development of adverse pregnancy complications. However, in India, there are limited population-based data to guide evidence-based recommendations and priority setting. The objective of this study is to conduct a population-based biomarker survey of anaemia and vitamin B12 and folate status in WRA as part of a periconceptional surveillance programme in Southern India. Methods: WRA (15–40 years) who are not pregnant or lactating and reside within 50 km 2 of our community research site in Southern India will be screened and invited to participate in the biomarker survey at our research facility at Arogyavaram Medical Centre. After informed consent/assent, structured interviews will be conducted by trained nurse enumerators to collect sociodemographic, dietary, anthropometry, health and reproductive history data. Venous blood samples will be collected at enrolment; whole blood will be analysed for haemoglobin. Plasma, serum and red blood cells (RBCs) will be processed and stored <−80°C until batch analysis. Vitamin B12 concentrations will be measured via chemiluminescence, and RBC and serum folate concentrations will be evaluated using the World Health Organisation (WHO)-recommended microbiological assay at our laboratory in Bangalore. A WHO surveillance system will also be established to determine the baseline prevalence of birth defects in this setting. Ethics and dissemination: This study has obtained clearance from the Health Ministry Screening Committee of the Indian Council of Medical Research. The study protocol was reviewed and approved by the Institutional Review Board at Cornell University and the Institutional Ethics Committees at Arogyavaram Medical Centre and St. John's Research Institute. Findings from this biomarker survey will establish the burden of anaemia and micronutrient deficiencies in WRA and directly inform a randomised trial for anaemia and birth defects prevention in Southern India. The results of this study will be disseminated at international research conferences and as published articles in peer-reviewed journals. Trial registration numbers: Clinical trials registration number NCT04048330, NCT03853304 and Clinical Trials Registry of India (CTRI) registration number REF/2019/03/024479.